Secondary messenger signalling influences Pseudomonas aeruginosa adaptation to sinus and lung environments - Dilem Ruhluel , Lewis Fisher , Thomas E. Barton , Hollie Leighton , Sumit Kumar , Paula Amores Morillo , Siobhan O’Brien , Joanne L. Fothergill , Daniel R. Neill (ISME, 2024)
Pseudomonas aeruginosa is a cause of chronic respiratory tract infections in people with cystic fibrosis (CF), non-CF bronchiectasis, and chronic obstructive pulmonary disease. Prolonged infection allows the accumulation of mutations and horizontal gene transfer, increasing the likelihood of adaptive phenotypic traits. Adaptation is proposed to arise first in bacterial populations colonizing upper airway environments. Here, we model this process using an experimental evolution approach. Pseudomonas aeruginosa PAO1, which is not airway adapted, was serially passaged, separately, in media chemically reflective of upper or lower airway environments. To explore whether the CF environment selects for unique traits, we separately passaged PAO1 in airway-mimicking media with or without CF-specific factors. Our findings demonstrated that all airway environments—sinus and lungs, under CF and non-CF conditions— selected for loss of twitching motility, increased resistance to multiple antibiotic classes, and a hyper-biofilm phenotype. These traits conferred increased airway colonization potential in an in vivo model. CF-like conditions exerted stronger selective pressures, leading to emergence of more pronounced phenotypes. Loss of twitching was associated with mutations in type IV pili genes. Type IV pili mediate surface attachment, twitching, and induction of cAMP signalling. We additionally identified multiple evolutionary routes to increased biofilm formation involving regulation of cyclic-di-GMP signalling. These included the loss of function mutations in bifA and dipA phosphodiesterase genes and activating mutations in the siaA phosphatase. These data highlight that airway environments select for traits associated with sessile lifestyles and suggest upper airway niches support emergence of phenotypes that promote establishment of lung infection.
PUBLISHED
Keywords: Pseudomonas aeruginosa; respiratory tract infection; within-host evolution; cyclic-di-GMP; cystic fibrosis; Immunology, Inflammation & Infection